The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/03079450500268583
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelas in the critically endangered kakapo (Strigops habroptilus)

Abstract: This paper describes the effect of a disease outbreak on the success of a translocation for conservation management in a critically endangered species. Three juvenile kakapo from a group of 19 translocated birds died within 72 h of transport between New Zealand offshore islands. Clinical findings, gross necropsy changes, cytology, histopathology and bacterial culture confirmed systemic disease caused by Erysipelothrix rhusiopathiae. On the island from which the kakapo were sourced, positive cultures of E. rhus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Such an event occurred in 2004, when three kakapo died from erysipelas within 72 hours of translocation. The birds had been checked for known pathogens [35], and erysipelas had not previously been observed in kakapo [36]. While attacks from previously unidentified pathogens are unavoidable, this highlights an area in which molecular microbiology could play a key role in aiding kakapo recovery efforts, through the use of specific, high-sensitivity molecular probing techniques to detect pathogens before their numbers expand to levels that affect the bird.…”
Section: Introductionmentioning
confidence: 99%
“…Such an event occurred in 2004, when three kakapo died from erysipelas within 72 hours of translocation. The birds had been checked for known pathogens [35], and erysipelas had not previously been observed in kakapo [36]. While attacks from previously unidentified pathogens are unavoidable, this highlights an area in which molecular microbiology could play a key role in aiding kakapo recovery efforts, through the use of specific, high-sensitivity molecular probing techniques to detect pathogens before their numbers expand to levels that affect the bird.…”
Section: Introductionmentioning
confidence: 99%
“…Necropsy and bacterial culture results confirmed that erysipelas was the cause of death of all three birds (Gartrell et al, 2005). These birds were among a group of 19 kakapo, 23% of the then world population of 83 birds, that had been transferred from one island sanctuary to another in July 2004.…”
Section: Introductionmentioning
confidence: 74%
“…Tests of mottled petrel (Pterodroma inexpectata) and sooty shearwater (Puffinus griseus) carcasses collected on Codfish Island indicated that 10 of 15 contained live E. rhusiopathiae bacillus (Gartrell et al 2005). Adults and chicks of these species were common on the island immediately prior to the 2004 transfer of kakapo to Chalky Island.…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 other reports of erysipelas in psittacines were found in the literature reviewed by the authors. 10,15 The use of IHC and PCR on paraffin-embedded tissues of confirmed and suspected cases of erysipelas in birds has not to been reported previously in the literature reviewed by the Galindo-Cardiel et al 499 Figure 1. Rainbow lorikeet, coelomic cavity.…”
mentioning
confidence: 95%